Affective temperament, attachment style, and the psychological impact of the COVID-19 outbreak: an early report on the Italian general population - Moccia, Lorenzo; Janiri, Delfina; Pepe, Maria; Dattoli, Luigi; Molinaro, Marzia; De Martin, Valentina; Chieffo, Daniela; Janiri, Luigi; Fiorillo, Andrea; Sani, Gabriele; Di Nicola, Marco (Brain, behavior, and immunity, 2020)
•The outbreak of COVID-19 is severely affecting mental health worldwide.•Individual response may vary according to background and specific features.•Temperament refers to early-appearing differences in emotional reactivity.•Adult attachment style modulates stress responsivity.•Temperament and attachment predict the psychological impact of the COVID-19 pandemic. The outbreak of COVID-19 is severely affecting mental health worldwide, although individual response may vary. This study aims to investigate the psychological distress perceived by the Italian general population during the early phase of the COVID-19 pandemic, and to analyze affective temperament and adult attachment styles as potential mediators. Through an online survey, we collected sociodemographic and lockdown-related information and evaluated distress, temperament, and attachment using the Kessler 10 Psychological Distress Scale (K10), the Temperament Evaluation of Memphis, Pisa, Paris and San Diego-Autoquestionnaire short version (TEMPS-A) and the Attachment Style Questionnaire (ASQ). In our sample (n = 500), 62% of the individuals reported no likelihood of psychological distress, whereas 19.4% and 18.6% displayed mild and moderate-to-severe likelihood. Cyclothymic (OR: 1.24; p < 0.001), depressive (OR: 1.52; p < 0.001) and anxious (OR: 1.58; p = 0.002) temperaments, and the ASQ “Need for approval” (OR: 1.08; p = 0.01) were risk factors for moderate-to-severe psychological distress compared to no distress, while the ASQ “Confidence” (OR: 0.89; p = 0.002) and “Discomfort with closeness” were protective (OR: 0.92; p = 0.001). Cyclothymic (OR: 1.17; p = 0.008) and depressive (OR: 1.32; p = 0.003) temperaments resulted as risk factors in subjects with moderate-to-severe psychological distress compared to mild distress, while the ASQ “Confidence” (OR: 0.92; p = 0.039) and “Discomfort with closeness” (OR: 0.94; p = 0.023) were protective. Our data indicated that a relevant rate of individuals may have experienced psychological distress following the COVID-19 outbreak. Specific affective temperament and attachment features predict the extent of mental health burden. To the best of our knowledge, these are the first data available on the psychological impact of the early phase of the COVID-19 pandemic on a sizeable sample of the Italian population. Moreover, our study is the first to investigate temperament and attachment characteristics in the psychological response to the ongoing pandemic. Our results provide further insight into developing targeted intervention strategies.